Advances in Biomaterials Science and Biomedical Applications - Pignatello, Rosario (IntechOpen, 2013)
This contribution book is a collection of reviews and original articles from eminent experts working in the multi- and interdisciplinary arena of biomaterials, ranging from their design to novel uses. From their personal experience, the readers can obtain a stimulating foresight on the potentialities of different synthetic and engineered biomaterials. 21 chapters have been organized to illustrate different aspects of biomaterials science. From advanced means for the characterization and toxicological assessment of new materials, through 'classical' applications in nanotechnology and tissue engineering, toward novel specific uses of these products, the volume wishes to give readers a view of the wide range of disciplines and methodologies that have been exploited to develop biomaterials with the physical and biological features needed for specific clinical and medical applications.